HUBUNGAN INDEKS MASA TUBUH DAN RIWAYAT DIABETES MELITUS DENGAN KEJADIAN HIPOGLIKEMIA PADA PASIEN HEMODIALISIS DI RUANGAN HEMODIALISA DI RSUD KISA KOTA DEPOK TAHUN 2025 - Ariska Dwi Febrianti; Susaldi Susaldi; Yani Handayani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Hypoglycemia is one of the common complications in patients with end-stage chronic kidney disease undergoing hemodialysis therapy. Nutritional status, measured by Body Mass Index (BMI), and a history of Diabetes Mellitus (DM) are suspected to contribute to the occurrence of hypoglycemia. This study aimed to determine the relationship between BMI and history of DM with the incidence of hypoglycemia among hemodialysis patients at Khidmat Sehat Afiat (KiSA) Regional Public Hospital, Depok City. This study employed a quantitative method with an observational analytic design and a cross-sectional approach. The sample consisted of 145 hemodialysis patients selected using a total sampling technique. Data were obtained from medical records and analyzed using the Chi-Square test. The results showed that the majority of hemodialysis patients were classified as obese based on BMI, while most patients did not have a history of DM. Bivariate analysis demonstrated a significant relationship between BMI and the incidence of hypoglycemia among hemodialysis patients (p value = 0.001; p < 0.05). In addition, a significant relationship was found between a history of DM and the incidence of hypoglycemia in hemodialysis patients (p value = 0.001; p < 0.05). In conclusion, BMI and history of DM are significantly associated with the incidence of hypoglycemia in hemodialysis patients. It is recommended that healthcare providers conduct appropriate screening and optimal blood glucose monitoring based on patients’ nutritional status and history of DM.